أداء المصرف التجاري السوري في ظل المتغيرات السورية الراهنة - هرمز, نور الدين; قاسم, سامر; سلمان, غيداء (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يهدف هذا البحث لدراسة أداء النظام المصرفي السوري في ظل المتغيرات التي بدأت في سورية منذ آذار 2011 والآثار المترتبة عليها( حالة المصرف التجاري السوري).وقد تبين من خلال البحث أن القطاع المصرفي قد تعرض إلى تداعيات أدت إلى عدم استقراره، الأمر الذي حدّ من دور المصارف كوسيط مالي يدعم الإنتاج ويشجع الاستثمار في مختلف قطاعات الاقتصاد الوطني, إضافة إلى تقليص حجم الخدمات التي تقدمها المصارف, وتغير أسعار الصرف وأزمة السيولة والائتمان. تم الاعتماد على بيانات التقارير المالية المنشورة على موقع المصرف التجاري السوري خلال الفترة من 2010- 2013.This research aims to study the Syrian banking system performance in light of changes that began in Syria since March 2011 and their implications (the case of Commercial Bank of Syria).It was found that the banking sector exposure to fallout led to instability, which limited the role of as a financial intermediary supporting production and encourage investment in the various national sectors of the economy, in addition to reducing the volume of services provided by banks, and changes in exchange rates, and a crisis of liquidity and credit.The research has been relying on financial reports which is published on the case of Commercial Bank of Syria site during the period from 2010 to 2013.